The Yugoslav idea in the first half of the 1990s - Korzeniewska-Wiszniewska, Mirella (Balcanica Posnaniensia. Acta et studia, 2009)
The article addresses the functioning and transformation of the Yugoslav idea during the collapse of the Socialist Federal Republic of Yugoslavia (SFRY) at the turn of the 1980s and 1990s. The starting point is an analysis of the social, political and economic factors that significantly contributed to the weakening of federal ties and the strengthening of separatist tendencies. The aim of the study is to show the evolution of the Yugoslav idea in the context of growing ethnic conflicts, the development of nationalist ideologies and attempts to maintain the unity of the state by the federal authorities and selected political circles. The analysis is based on historical sources, party and state documents, and literature on the subject. The author uses a historical-political method, interpreting socio-political processes in an international context. The results of the study indicate that in the first half of the 1990s, the Yugoslav idea still had supporters, especially among some of the socio-political elites of the federation. However, pro-Yugoslav initiatives, present in official discourse, proved insufficient in the face of prevailing disintegration processes. The author concludes that the Yugoslav idea did not disappear completely, but underwent a transformation, becoming an element of ideological and political disputes in the Balkan region in the 1990s.